2003
DOI: 10.1096/fj.03-0122com
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive differences in the structure and macromolecular compositions of the air and water corneas of the “four‐eyed” fish (Anableps anableps)

Abstract: The water meniscus bisects the eyes of the "four-eyed" fish Anableps anableps, resulting in simultaneous vision in air and water. We compare the structure and macromolecular compositions of the Anableps dorsal (air) and ventral (water) corneas with the fully aquatic zebrafish cornea. The Anableps dorsal corneal epithelium is thicker (>20 cell layers), flatter (approximately 1.94 mm radius of curvature), and contains approximately 15-fold more glycogen (0.16 microg/microg water-soluble protein) than the ventral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 36 publications
2
44
0
Order By: Relevance
“…Since the corneal epithelium and the lens are both derived from ectoderm, it seems reasonable to propose that the evolution of transparency in these two structures may have co-evolved as an integrated 'refracton' unit. Indeed, data showing that the corneas from a diverse range of species including squid, fish, frogs, crocodiles, birds and mammals abundantly express a few water-soluble proteins is consistent with this theory [6,7,[9][10][11]13]. However, the vast majority of studies identifying corneal crystallin expression have used total corneal extracts or isolated corneal epithelium.…”
Section: Expression Of Corneal Crystallins In Corneal Keratocytesmentioning
confidence: 79%
See 1 more Smart Citation
“…Since the corneal epithelium and the lens are both derived from ectoderm, it seems reasonable to propose that the evolution of transparency in these two structures may have co-evolved as an integrated 'refracton' unit. Indeed, data showing that the corneas from a diverse range of species including squid, fish, frogs, crocodiles, birds and mammals abundantly express a few water-soluble proteins is consistent with this theory [6,7,[9][10][11]13]. However, the vast majority of studies identifying corneal crystallin expression have used total corneal extracts or isolated corneal epithelium.…”
Section: Expression Of Corneal Crystallins In Corneal Keratocytesmentioning
confidence: 79%
“…Later studies have identified BCP54 as aldehyde dehydrogenase 3A1 [4,5] that comprises from 20-40% of the total water-soluble protein content of the bovine corneal epithelium. More recent studies have shown that unlike non-transparent tissues and organs other than lens, the corneas from a wide range of species abundantly express a few water-soluble enzyme/proteins (Table 1) [3,[6][7][8][9][10][11][12][13][14], many of which are identical to the abundantly expressed taxon-specific lens crystallins, including aldehyde dehydrogenase 1A1 (ALDH1A1)/η-crystallin, α-enolase/τ-crystallin, glutathione-S-transferase/Ω-crystallin, lactic dehydrogenase/ε-crystallin, glyceraldehyde-3-phosphate dehydrogenase (G3PDH)/π-crystallin, and arginino-succinate lyase/δ-crystallin [6,8]. Interestingly, several of these corneal enzyme/proteins are abundantly expressed in the lens of the same species, notably argininosuccinate lyase/δ-crystallin in the chicken and glutathione-S-transferase/Ω-crystallin in the squid.…”
Section: Introductionmentioning
confidence: 99%
“…At the peripheral limbal region, the stroma splits into multiple layers. Just beneath the stroma is a single layer of cells overlying a second, thinner stromal layer with similar collagen organization (Figure 3K, [15]). Subjacent to these cells, an additional collagen-rich extracellular layer can be seen with electron microscopy (Descemet's membrane).…”
Section: Resultsmentioning
confidence: 99%
“…Like other vertebrates, the zebrafish cornea is avascular. The adult zebrafish cornea has been characterized histologically and ultrastructurally (Swamynathan et al, 2003; Soules and Link, 2005; Zhao et al, 2006; Akhtar et al, 2008). When mature, it is approximately 20 microns thick.…”
Section: A the Cornea And Lensmentioning
confidence: 99%